Homolka, Walter. 2025. Nie jest dobrze, by człowiek był sam. Zaręczyny, małżeństwo i rozwód w tradycji prawa żydowskiego, 366. Poznań: Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza - Gałkowski, Tomasz (Prawo Kanoniczne, 2026)
Walter Homolka discusses and explains the traditions and legal norms that have governed – and continue to govern – the conclusion of a Jewish religious marriage. The author also addresses contemporary issues concerning the relationship between religious law and state law in the countries in which Jewish communities have developed within different traditions (Neo-Orthodox, Conservative, and Liberal Judaism). This work is not, however, a monograph in the form of a commentary on binding law. Rather, the author skillfully introduces the subject by presenting the nature of the religious community, its history, and its continuity under adverse conditions, in which law becomes one of the guarantees of unity and stability of the chosen people. The study not only enables the reader to explore the complexities of Jewish matrimonial law, but also outlines a perspective for dialogue between Jewish matrimonial law and the matrimonial law of the Church, firmly rooted in Roman and Germanic legal traditions.